Understanding Extraordinary Architectural Experiences through Content Analysis of Written Narratives - Ro, Brandon Richard; Bermudez, Julio (Enquiry The ARCC Journal for Architectural Research, 2015)
This study a) identifies how people describe, characterize, and communicate in written form Extraordinary Architectural Experiences (EAE), and b) expands the traditional qualitative approach to architectural phenomenology by demonstrating a quantitative method to analyze written narratives. Specifically, this study reports on the content analysis of 718 personal accounts of EAEs. Using a deductive, ‘theory-driven’ approach, these narratives were read, coded, and statistically analyzed to identify storyline structure, convincing power, and the relationship between subjective and objective experiential qualities used in the story-telling process. Statistical intercoder agreement tests were conducted to verify the reliability of the interpretations to approach the hard problem of "extraordinary aesthetics” in architecture empirically. The results of this study confirm the aesthetic nature of EAE narratives (and of told experiences) by showing their higher dependence on external objective content (e.g., a building’s features and location) rather than its internal subjective counterpart (e.g., emotions and sensations), which makes them more outwardly focused. The strong interrelationships and intercoder agreement between the thematic realms provide a unique aesthetic construct revealing EAE narratives as memorable, embodied, emotional events mapped by the externally focused content of place, social setting, time, and building features. A majority of EAE narratives were found to possess plot-structure along with significant relationships to objective-subjective content that further grounded their storylines. This study concludes that content analysis provides not only a valid method to understand written narratives about extraordinary architectural experiences quantitatively, but also a view as to how to map the unique nature of aesthetic phenomenology empirically.